An unusual site for renal metastasis: A pictorial presentation - Köse, Muammer Müslim; Durmuş, Oğuz; Ayhan, Mustafa Yemliha; Keskinbora, Mert; Örmeci, Tuğrul (Elsevier, 2014)
The differential diagnosis of shoulder pain and restricted motion includes primary or metastatic cancer. Common cancers, such as breast, prostate, thyroid, lung, and renal, frequently metastasize to bone [1]. Bone metastasis is rarely asymptomatic, rather triggering refractory and persistent bone pain. Osteolysis is accompanied by increased bone fragility and pathologic fractures. These typically occur in weight-bearing bones such as the femur or pelvis. Breast, lung, and renal metastases cause extensive bone destruction and pain [2].
WOS: 000346402700015
PubMed ID: 24982001
Keywords: Renal Metastasis; Cancer; Bone